Associative learning of concepts - Rockai, Viliam; Kende, Robert (Computer Assisted Methods in Engineering and Science, 2022)
Humans find it extremely easy to say if two words are related or if one word is more related to a given word than another one. For example, if we come across two words - 'car' and 'bicycle', we know they are related since both are means of transport. Also, we easily observe that 'bicycle' is more related to 'car' than 'fork' is. In the paper we describe our approach on quantifying the semantic relatedness of concepts based on the theory of associative learning of concepts.